SISTEM INFORMASI TUGAS PEGAWAI UNTUK ADMIN, PENANGGUNG JAWAB DAN PENGENDALI TEKNIS DPMPTSP KABUPATEN BANYUWANGI - Nabila Nabila; Ahmad Homaidi; Medi Sugiarto (Jurnal Riset Teknik Komputer, 2025)
The increasing demand for digital transformation in the public sector has encouraged government institutions to optimize their performance through information systems. This study was carried out at the Investment and One-Stop Integrated Service Office (DPMPTSP) of Banyuwangi Regency still faces challenges in monitoring employee tasks, which are carried out manually and prone to delays, lack of transparency, and imbalance of workloads. This research aims to design a web-based Employee Task Monitoring Information System (SIMANTAP) to support effective and accountable task management. The methodology adopted in this research was the Research and Development (R&D) framework, implemented through the waterfall development model for system development. The data were gathered using several techniques, namely interviews, direct observation, and a review of relevant literature. The system design process involved the preparation of use case diagrams, activity diagrams, sequence diagrams, class diagrams, as well as a database schema, and user interface prototypes using Draw.io and Figma. The outcome of this study is a system design which allows administrators, supervisors, and technical controllers to monitor, assign, and evaluate employee tasks in real time. This system is expected to improve transparency, workload distribution, and performance evaluation within DPMPTSP Banyuwangi. Beyond the conceptual contribution, the design also provides practical value by supporting daily task management in government institutions, making work supervision more efficient and accountable.